2010
DOI: 10.1111/j.1365-2702.2010.03421.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in pregnant women and their quality of life

Abstract: This study reveals that the prevalence of urinary incontinence during pregnancy is very high. The findings will help increase the awareness of health care workers involved in the care of pregnant women about urinary incontinence and aid the design of more intensive education programmes directed towards the prevention of urinary incontinence during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
87
1
23

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(127 citation statements)
references
References 40 publications
16
87
1
23
Order By: Relevance
“…(26) Authors evaluated 393 pregnant women using the ICIQ-SF as a tool to assess the quality of life of incontinent pregnant women, and they had one in their findings mean score of 9.9 points. (27) Another study, which evaluated 746 women of different ethnicities pregnant women, observed similar results, ie, the ICIQ-SF score ranged from 5.4 to 8.6 points. (18) The findings of these studies are similar to this, although the sample size to be different.…”
Section: Evaluation Of the Knowledge Of The Perineal Regionsupporting
confidence: 50%
“…(26) Authors evaluated 393 pregnant women using the ICIQ-SF as a tool to assess the quality of life of incontinent pregnant women, and they had one in their findings mean score of 9.9 points. (27) Another study, which evaluated 746 women of different ethnicities pregnant women, observed similar results, ie, the ICIQ-SF score ranged from 5.4 to 8.6 points. (18) The findings of these studies are similar to this, although the sample size to be different.…”
Section: Evaluation Of the Knowledge Of The Perineal Regionsupporting
confidence: 50%
“…Moreover, specific hormonal alterations during this period reduce muscle tonus and strength 1 , predisposing pregnant woman to PFM dysfunctions such as urinary incontinence (UI), fecal incontinence (FI), pelvic organ prolapse (POP) and sexual dysfunction 2,3 . The prevalence of UI during pregnancy is high, ranging from 24.3% to 63.8% in several studies [4][5][6][7][8] . In a Cochrane Library systematic review, Hay-Smith et al 9 evaluated the effects of pelvic floor muscle training (PFMT) on UI in pregnant women and concluded that women who undertook such training reported less UI during pregnancy, which supports the routine recommendation of PFMT during prenatal care.…”
Section: Introductionmentioning
confidence: 99%
“…Kocaoz et al [35], in a study of 393 pregnant women, found that their quality of life was either unaffected or very little affected by urinary incontinence. In addition, they also observed that only a few of those women sought help from a healthcare professional [36][37][38].…”
Section: Discussionmentioning
confidence: 99%